Analisis Puisi Pada Hari Minggu Kucari Ayah ke Kota Karya Hasan Aspahani Ditinjau dari Aspek Semiotik - Adeline, Sheyla; Arifin, Syaiful; Indrahastuti, Tri (Adjektiva: Educational Languages and Literature Studies, 2019)
This study aims to describe the shape of the icons, indexes, and symbols contained in the poem On Sunday I’m Looking For My Father To The City. The method used in this research is a qualitative approach method. Data collection techniques used are library research techniques, reading techniques, note-taking techniques, and semi-structured interview techniques. The data analysis techniques used is to understand the data as a whole, classify the data,make comparisons of data matches, and draw data conclusions. The results of this study include (1) Icons in the poem On Sunday I Look for Father to The City by Hasan Aspahani there two types of icons, namely image icons and diagrammatic icons.(2) The index in the poem On Sunday I’m Looking for My Father to The City by Hasan Aspahani is an index in various findings between texts.(3) Symbols in Hasan Aspahani’s poem On Sunday I Look for Father to the City are signs that do not show a casual relationship between the signifier and the signifier.